Teachers’ Learning Reinforcement: Effects on Students’ Motivation, Self Efficacy and Academic Performance - S. Macalisang, Denmark; G. Bonghawan, Rouan Grace (International Journal of Scientific Research and Management (IJSRM), 2024)
Teachers play an important role in shaping the educational experiences and achievements of students. As education continues to evolve, it is essential to explore innovative approaches that can enhance teaching effectiveness and improve student outcomes. This study was conducted to determine the teachers’ learning reinforcement and its effects to student’s motivation, self-efficacy and academic performance. A total of thirty five (35) classroom teachers and two hundred sixty (262) Criminology students of Southern Capital Colleges participated in the study during the academic year 2022-2023. Weighted Mean, Standard Deviation, Frequency Count and Percentage, and Spearman Rho Correlation Coefficient were the statistical tools used in the study. The teachers consistently employed various reinforcement strategies, demonstrating their commitment to supporting students’ educational experiences. Students exhibited positive self-efficacy beliefs, indicating confidence in their abilities to succeed and overcome challenges. It also displayed satisfactory levels of motivation, showing a genuine interest in challenging course content and a focus on deep understanding. Furthermore, there were significant relationships between teachers’ learning reinforcement and students’ self-efficacy, motivation, and academic performance. Effective learning reinforcement positively influenced students’ beliefs in their abilities, motivating them to persist and excel in their studies. An emphasis on the importance of implementing effective learning reinforcement in educational settings is paramount to enhance students’ educational experiences and promote academic success.